The Piano Music of Percy Grainger: A Pianist's Perspective on Pedalling - Carruthers, Glen (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2001)
Eminent pianist and composer Percy Aldridge Grainger (1882–1961) filled his original music and folksong arrangements with detailed, though idiosyncratic instructions to performers. The extent to which his own meticulous pedal technique is mirrored in careful directions to pianists is both unusual and revelatory. Grainger's scores are examined here from the standpoint of the damper, sostenuto and una corda pedals. Numerous musical examples serve two purposes: 1) they give information concerning the complexity of Grainger's pedal technique and 2) they exhibit the array of notational methods the composer employed, at various stages in his career, to enable performers to replicate as nearly as possible his own scrupulous pedalling. As well, by examining in detail this one aspect of Grainger's rich artistry, light is shed on the relationship between composer and performer, and notation and interpretation, that Grainger sought to understand and articulate ever more clearly throughout his career.